Environmental and Anthropogenic Factors Affect Fish Abundance: Relationships Revealed by Automated Cameras Deployed by Fishers - Brooker, Michael A.; de Lestang, Simon; Fairclough, David V.; McLean, Dianne; Slawinski, Dirk; Pember, Matthew B.; Langlois, Tim J. (Frontiers in Marine Science, 2020)
Understanding the drivers of fish abundance distributions is key to successful natural resource management, but it is costly to obtain this information at large spatio-temporal scales relevant to management. We used small programmable video cameras deployed in commercial rock lobster fisher’s pots, during normal fishing activities, across ~750 kilometers of the west coast of Australia (10-120 m deep), to test for relationships between the relative abundance of fishes and both environmental (habitat composition, swell, depth and water temperature) and anthropogenic factors (recreational and commercial fishing effort). Among the six most frequently observed fishes, the abundances of two targeted species, Choerodon rubescens and Epinephelides armatus, were negatively correlated with an index of recreational effort, although this was confounded by the natural abundance distribution of these species along the west coast. For example, a unimodal abundance distribution with latitude was observed for the endemic labrid C. rubescens, matching its known distribution. In contrast, the abundances of the commercially important Chrysophrys auratus and Lethrinus miniatus were positively correlated with an index of commercial effort, reflecting the expectation that commercial fishers typically would target areas of greatest abundance that produce high catches per unit effort. The abundances of Coris auricularis and Neatypuus obliquus (non-target species) were correlated with expected environmental variables (water temperature, depth, habitat composition and swell) but neither recreational or commercial fishing effort. All but one of the species investigated had a strong positive relationship with reef cover, as expected for these reef species, and three species exhibited a negative relationship with swell. We have developed a highly cost-effective fisheries-independent monitoring tool to understand relationships between species abundance distributions and major environmental and anthropogenic factors. It is easily deployed using existing pot or trap fishery infrastructure and can and is therefore highly applicable to both developed and developing countries.